Ang Tadyang ni Adan [videorecording] - Bautista, Lualhati; Bernal, Ishmael; Castro, Butch S.; Lagera, Rudy J.; Montemayor, Myrna (Hasik, 1990)
Tackles gender issues in Philippine setting. A TV drama revolving around the problems of a Filipino family.